PERGESERAN MAKNA PRIYAYI DALAM NOVEL PARA PRIYAYI KARYA UMAR KAYAM - Rudi Ekasiswanto (POETIKA, 2013)
"> AbstractThis study aims to determine the meaning of priyayi and its shift in Umar Kayam’s Para Priyayi. The theoryused in this study is the theory of hegemony Gramsci. The method used is descriptive and analytical methods. Descriptivemethod is used to describe the social aspects of novel Para Priyayi, while analytical methods is used to analyze novel ParaPriyayi combining hegemony Gramsci. Para Priyayi containing values and meanings shift of Javanese noble. In addition,the values infiltrated by the author; Umar Kayam as humanists, academics, writers, the Javanese, also gives hiss own view.The emergence of multiple views, of course, establishes and leads a fight existing value of each character in the story. Theprocess happen allegedly contained negotiation among values. It is seen in moving process of humble class toward nobleclass. The process of negotiation among characters is represented in figures Sastrodarsono and Lantip or the fights amongpeople in noble class their self. Such processes continue to be made to reach consensus and truth together.Keywords: priyayi, the humble, the transformation of values, concencuss, negotiation, and hegemonic analysis